Scientific echosounder data provide a predator’s view of Antarctic krill (Euphausia superba) - Cox, M. J.; Smith, A. J. R.; Brierley, A. S.; Potts, J. M.; Wotherspoon, S.; Terauds, A. (Scientific Data, 2023)
Funding: The KAOS voyage was supported by Australian Antarctic Science (AAS) grant 2205 and this data processing by AAS grants 4050 and 4636. Raw acoustic data were collected in East Antarctica from the RSV Aurora Australis during two surveys: the Krill Availability, Community Trophodynamics and AMISOR Surveys (KACTAS) and the Krill Acoustics and Oceanography Survey (KAOS) in the East Antarctic (centre coordinate 66.5° S, 63° E). The KACTAS survey was conducted between 14th to 21st January and 2001, and the KAOS survey was conducted between 16 January and 1 February 2003. We examine the Antarctic krill (Euphausia superba) component of these surveys and provide scientific echosounder (EK500 and EK60) data collected at 38, 120 and 200 kHz, cold water (−1 °C) echosounder calibration parameters and accompanying krill length frequency distributions obtained from trawl data. We processed the acoustic data to apply calibration values and remove noise. The processed data were used to isolate echoes arising from swarms of krill and to estimate metrics for each krill swarm, including internal density and individual swarm biomass. The krill swarm data provide insights to a predators’ views of krill distribution and density. Peer reviewed